The Crucial Role of School Leaders' Administrative Support in the ResearchCapability of Teachers (Journal of School Administration Research and Development, 2026)
Research on educators' research capability has surged in recent years, as scholars and practitioners remain intrigued by how teachers develop investigative skills alongside pedagogical mastery. To ensure evidence-based decision-making, policy formulation, and program development, school leaders must inspire teachers to contribute empirical evidence. However, previous literature has often neglected the link between teachers' research capability and the administrative support provided by school leaders. To address this gap, an explanatory study was conducted to examine the crucial role of administrative support in enhancing these capabilities. The study was conducted in the Quezon II District of Bukidnon, Philippines, and involved 151 teachers who voluntarily responded to survey instruments. After analyzing datasets using descriptive and inferential statistics, the findings indicated that while administrative support was frequently observed across all dimensions, teachers demonstrated only moderate proficiency in writing research proposals and publishable papers. The tested models revealed a nuanced relationship between support and capability, and the dimensions of administrative support did not significantly explain research capability when analyzed individually. When these dimensions were integrated into hypothesized models, administrative support significantly predicted teachers' research capability, accounting for 10.9%-12.2% of the variance in research capability. Ultimately, school leaders' administrative support plays a vital role in enhancing teachers' capability in writing research proposals and publishable papers. The study infers that each component of support is indispensable; only through a holistic approach can school leaders effectively elevate teachers' research capabilities.